ENZYME-PRODUCING GUT BACTERIA OF FISH AND ITS EFFECT ON FISH HEALTH: A REVIEW - SARMAH, PUJA; KARDONG, DEVID (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Like all multicellular organisms fish also lives in close association with microorganisms. They live in a symbiotic relationship and the bacteria provide protection, immunity and metabolic strength to the host and in return, the host gives nutrient-enriched media to it. Gut microbes of fish secret amylase, lipase, cellulase, protease, chitinase etc. and they play a significant role in digestion. To date, most of the studies on gut microbiota have emphasized the mammal. Contrary to this, information about the host-microbe interactions in fishes is limited. Therefore, a better understanding of this topic is the need of the hour. Exogenous enzymes can be produced by the gut microbes such as Lactobacillus spp., Pseudomonas spp., and Vibrio spp. etc to improve the digestion of food and degradation of complex and large molecules, such as protein, starch, and chitin. Similarly, when the composition of microbiota changes many biosynthesis and metabolism pathways of carbohydrates, amino acids, and lipids also change. Epithelial absorption of fatty acid is facilitated by the colonization of the gut microorganisms, this colonization also protects the host against pathogenic bacteria. To achieve sustainable disease control and nutrient enhancement strategies in aquaculture practices an understanding of the dynamics and functions of the gut microbial community in fish is necessary as it will enable a more profound selection of the beneficial microorganisms.